2021
DOI: 10.1002/mame.202000668
|View full text |Cite
|
Sign up to set email alerts
|

Biobased Polyester‐Amide/Cellulose Nanocrystal Nanocomposites for Food Packaging

Abstract: The worldwide plastic waste production is steadily increasing, since the use of polymeric materials continues to rise. One area of particular high plastic consumption is food packaging. Flexible and rigid packaging films are typically made from petrochemical‐sourced polymers, which are utilized because of their low cost, ductility, melt‐processability, and gas barrier properties, but a major downside is their inability to biodegrade in a reasonable time. Packaging‐relevant properties of nanocomposites based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…[30][31][32] One way to improve the properties of polymer composites is to use nanoparticles. 33 Loading inorganic particles can improve many drawbacks of PLA such that enhance the strength of the PLA melt, improve PLA foaming behavior, and accelerate the kinetics of PLA crystallization. 34 It has also been proposed that loading crystal nucleating agents are the reason for crystallization takes place at a higher temperature or a faster cooling rate.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] One way to improve the properties of polymer composites is to use nanoparticles. 33 Loading inorganic particles can improve many drawbacks of PLA such that enhance the strength of the PLA melt, improve PLA foaming behavior, and accelerate the kinetics of PLA crystallization. 34 It has also been proposed that loading crystal nucleating agents are the reason for crystallization takes place at a higher temperature or a faster cooling rate.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review [11] confirmed that consumers are aware and informed of the need to avoid or reduce their use of plastic packaging materials. However, this is not always possible in practice, since the use of plastic for packaging has increased, and various food and beverage packaging applications and polymer modifications have been developed [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…For fillers with surface modifications based either on ionic exchange or grafting of molecules of different chain lengths and mobilities, the existence and significant role played by this third phase on the barrier properties have been experimentally proven [ 38 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. In some cases, the barrier properties are enhanced by the presence of the interphase due to stronger filler–matrix interfacial interactions [ 32 , 35 , 60 , 61 , 62 ]. In other cases, increased mobility or a lack of packing density in the interphase region lead to degradation of the barrier effect [ 51 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rader at al. [ 32 ] reported oxygen transmission rate (OTR) reductions of as much as 40% for a CNC content of 10 wt% within a bio-based polyester-amide (PEA) matrix. It was shown that the barrier enhancement was highly dependent on the composition of the PEA matrix but much less so on the CNC content.…”
Section: Introductionmentioning
confidence: 99%